Genomic and geochemical identification of the long-chain alkenone producers in the estuarine Lake Takahoko, Japan: Implications for temperature reconstructions. (April 2020) - Kajita, Hiroto; Nakamura, Hideto; Ohkouchi, Naohiko; Harada, Naomi; Sato, Miyako; Tokioka, Shun; Kawahata, Hodaka
Highlights: We discovered LCAs in the brackish Lake Takahoko, in northern Japan. Two distinct Group II haptophytes are responsible for LCAs production. Lake Takahoko may be suitable for alkenone paleotemperature reconstruction. Abstract: Identifying the lacustrine haptophyte species that produce long-chain alkenones (LCAs) is essential for using alkenone unsaturation ratios to create lake water temperature reconstructions. We discovered LCAs in the brackish Lake Takahoko in northern Japan. The identity of LCA-producing species was investigated using 18S ribosomal DNA (rDNA) and organic geochemical analysis. Two distinct genetic groups, termed Tak-A and Tak-B, were identified within the Group II haptophyte phylotype. Tak-A was closely related to Hap-A, which was obtained from Lake George, USA; and Tak-B was identified as Isochrysis galbana . Because Hap-A and Isochrysis galbana have similar temperature calibrations, Tak-A and Tak-B were also expected to share similar calibrations. Therefore, the changes of their relative abundances in the lake should not significantly disturb paleotemperature reconstructions. The alkenone temperature recorded in the surface sediment corresponded to the lake temperature in early to late summer. This is likely related to the haptophyte bloom season in Lake Takahoko suggesting that this lake may be a viable location for creating a lacustrine alkenone paleotemperature record.